Intention to initiate and uptake of PrEP among women who injects drugs in a demonstration project: an application of the theory of planned behavior. Issue 6 (3rd June 2021) - Tran, Nguyen K.; Felsher, Marisa; Pol, Barbara Van Der; Bellamy, Scarlett L.; McKnight, Jade; Roth, Alexis M.
ABSTRACT: Some women who inject drugs (WWID) would benefit from pre-exposure prophylaxis (PrEP), yet there are few studies of issues related to uptake in real-world settings. In this study, participants ( n  = 95) were offered PrEP and responded to items measuring PrEP-related attitudes, norms, and perceived behavioral control based on the Theory of Planned Behavior. We tested associations with intention to initiate PrEP and uptake. Most WWID (88%) intended to initiate PrEP and 78% accepted a prescription. Compared to WWID who did not express PrEP intentions, those who did were less concerned about attitudinal and perceived behavioral control constructs such as temporary (75% vs. 36%, p  = 0.01) and long-term (63% vs. 27%, p  = 0.05) side effects, negative interactions with their birth control (93% vs. 38%, p  < 0.01), their ability to take a daily pill (80% vs. 36%, p  < 0.01), and the cost of PrEP (87% vs. 36%, p  < 0.01). WWID who went on to take PrEP had fewer concerns with subjective norms constructs such as talking to health care providers about sex (91% vs. 65%, p  < 0.01) and drug use (88% vs. 55%, p  < 0.01) compared to those who did not. Attitudes and perceived behavioral control influenced intention while subjective norms had a greater impact on actual uptake.